Pengaruh Promosi, Persepsi Kemudahan dan Kepercayaan terhadap Loyalitas Pelanggan GrabFood di Kota Batam - Nainggolan, Sri Yuliana Br; Sukati, Inda (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The increasing dependence on digital platforms for food delivery services has reshaped consumer behavior in Indonesia, with GrabFood emerging as one of the most prominent players. However, inconsistencies in promotional strategies, usability concerns, and lapses in service quality have raised questions about customer loyalty in specific regions such as Batam City. This study aims to investigate the extent to which promotion, perceived ease of use, and consumer trust influence customer loyalty toward GrabFood in Batam. A quantitative descriptive approach was adopted, targeting active GrabFood users as the population. Using purposive sampling and the Jacob Cohen formula, 204 valid responses were collected. Data analysis involved instrument validity and reliability testing, classical assumption verification, multiple linear regression analysis, and hypothesis testing using both t-tests and F-tests. The empirical results demonstrate that promotion, perceived ease of use, and trust each have a statistically significant and positive influence on customer loyalty, both individually and collectively. Specifically, promotion contributes 15.0%, perceived ease of use contributes 18.6%, and trust contributes 16.8% to loyalty. Together, the three variables explain 71.0% of the variance in customer loyalty, as indicated by the adjusted R² value. These findings suggest that loyalty among GrabFood users in Batam is strongly shaped by effective promotional engagement, seamless user experience, and consistent service reliability. Strengthening these factors could enhance customer retention in a competitive food delivery market.